1986
DOI: 10.1128/jvi.60.1.204-214.1986
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements and insertions in the Moloney murine leukemia virus long terminal repeat alter biological properties in vivo and in vitro

Abstract: The effects of rearrangement and insertion of sequences in the Moloney murine leukemia virus (M-MuLV) long terminal repeat (LTR) were investigated. The alterations were made by recombinant DNA manipulations on a plasmid subclone containing an M-MuLV LTR. Promoter activity of altered LTRs was measured by fusion to the bacterial chloramphenicol acetyltransferase gene, followed by transient expression assay in NIH 3T3 cells. M-MuLV proviral organizations containing the altered LTRs were also generated, and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The AMo+G/C LTR was derived from the AMo LTR by restoration of the GC-rich sequences downstream from the tandem repeats (-180 to -150 bp). Polyomavirus FIOI (PyF101) enhancer sequences inserted into the wildtype, zvMo, and Mo+ LTRs have been described previously (5,6,23 Expression of PyFlOl-containing LTRs. Gorman et al 12previously suggested that the inability of the Moloney murine sarcoma virus LTR (closely related to the MoMuLV LTR) to function in undifferentiated F9 EC cells may be due to the presence of dominant negative regulatory factors in F9 EC cells that interact with the tandem repeats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMo+G/C LTR was derived from the AMo LTR by restoration of the GC-rich sequences downstream from the tandem repeats (-180 to -150 bp). Polyomavirus FIOI (PyF101) enhancer sequences inserted into the wildtype, zvMo, and Mo+ LTRs have been described previously (5,6,23 Expression of PyFlOl-containing LTRs. Gorman et al 12previously suggested that the inability of the Moloney murine sarcoma virus LTR (closely related to the MoMuLV LTR) to function in undifferentiated F9 EC cells may be due to the presence of dominant negative regulatory factors in F9 EC cells that interact with the tandem repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular cloning procedures were performed by standard protocols (26). Construction of LTR-chloramphenicol acetyltransferase (CAT) gene fusion plasmids has been described previously (6,14,23). Isolation of the F9 EC cellular enhancer element has also been described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of proviral DNA in tumors and molecular characterization. Genomic DNAs were harvested from the spleen, thymus, and lymph nodes of moribund leukemic mice as previously described (19). Restriction endonuclease digestion of genomic DNA (5 g), agarose gel electrophoresis (0.8% agarose), and transfer to GeneScreen Plus (New England Nuclear) were performed as described previously (19).…”
Section: Construction Of Recombinant Provirus and Production Of An Inmentioning
confidence: 99%
“…Genomic DNAs were harvested from the spleen, thymus, and lymph nodes of moribund leukemic mice as previously described (19). Restriction endonuclease digestion of genomic DNA (5 g), agarose gel electrophoresis (0.8% agarose), and transfer to GeneScreen Plus (New England Nuclear) were performed as described previously (19). Hybridization probes included the random primed SRS enhancer PCR fragment for the detection of input ⌬MoϩSRS ϩ and ⌬MoϩSRS Ϫ M-MuLVs, as well as DNA fragments containing c-myc, Pim-1, Pvt-1, T-cell receptor beta (TCR-␤), immunoglobulin heavy-chain (IgH), and Ig gene sequences for the molecular characterization of each tumor type as described previously (18).…”
Section: Construction Of Recombinant Provirus and Production Of An Inmentioning
confidence: 99%
“…We previously studied the role of enhancer sequences in gene expression and pathogenesis for M-MuLV. By molecular cloning, substitutions and insertions with heterologous viral enhancers resulted in chimeric LTRs that showed altered transcriptional properties in transient expression assays (11,13,18,36). Infectious M-MuLVs containing these altered LTRs also showed altered biological properties in tissue culture and in inoculated mice (10,17,18).…”
mentioning
confidence: 99%